Sodium–glucose cotransporter 2 inhibitors in type 2 diabetes patients with renal function impairment slow the annual renal function decline, in a real clinical practice. Issue 9 (20th February 2021) - Hirai, Taro; Kitada, Munehiro; Monno, Itaru; Oda, Erina; Hayashi, Yoshihiro; Shimada, Keiji; Takagaki, Yuta; Ogura, Yoshio; Fujii, Mizue; Konishi, Kazunori; Sakurai, Masaru; Nakagawa, Atsushi; et al.
Abstract: Aims/Introduction: The aim of this study was to elucidate whether sodium–glucose cotransporter 2 inhibitors (SGLT2is) treatment has any renoprotective effect for type 2 diabetes mellitus patients with an estimated glomerular filtration rate (eGFR) of <60 mL/min/1.73 m 2 in clinical practice. Materials and Methods: We evaluated the annual eGFR slope in 85 type 2 diabetes mellitus patients with renal impairment, treated with SGLT2is ≥2 years. Each patient's eGFR was <60 mL/min/1.73 m 2 at the start of SGLT2is therapy. The calculation of the annual change in eGFR for each patient was obtained by acquired eGFR data before and after 2 years of the initial SGLT2is administration, followed by analysis of the changes in the mean eGFR slope. Results: The participants' mean age was 72.0 ± 9.4 years, and the mean eGFR was 47.1 ± 9.7 mL/min/1.73 m 2 at the start of additional treatment with SGLT2is. The mean annual eGFR slope after SGLT2is administration (−0.11 ± 0.20 mL/min/1.73 m 2 /year) was significantly slower than before SGLT2is administration (−2.93 ± 0.59 mL/min/1.73 m 2 /year; P < 0.0001). Additionally, SGLT2is treatment slowed the annual decline of eGFR, independent of the levels of both the initial eGFR and albuminuria levels before SGLT2is therapy was started. In the patient groups who showed an annual eGFR decline of ≥3 and 1–3 mL/min/1.73 m 2, there was a significant slowing of the decline after SGLT2is therapy, compared with before the treatment ( P < 0.001, respectively). Conclusions: SGLT2is administration slows the decline observed in the annual renal function in type 2 diabetes mellitus patients with eGFR of <60 mL/min/1.73 m 2 in clinical practice. Abstract : Administration of sodium–glucose cotransporter 2 inhibitors slowed the annual estimated glomerular filtration rate decline in type 2 diabetes patients with an estimated glomerular filtration rate of <60 mL/min/1.73 m 2 .